Assessment of natural radioactivity and heavy metals in water and soil around seismically active area - Baykara, Oktay; Dogru, Mahmut (Springer, 2010)
The natural radioactivity concentration and some heavy metals in various water and soil samples collected from seismically active area have been determined. Gross-alpha and beta concentrations of different 33 water samples and some heavy metal (Fe, Pb, Cu, K, Mn, Cr and Zn) concentration in 72 soil samples collected from two major fault systems (North and East Anatolian Active Fault Systems) in Turkey have been studied. This survey regarding gross-alpha and beta radioactivity and some heavy metals concentrations was carried out by means of Krieger method using a gross-alpha and beta-counting system and atomic absorption spectrometry (AAS), respectively. Also, gross annual effective dose from the average gross-alpha activity in waters were calculated.
Keywords: Gross alpha and beta; Fault systems; Heavy metals; Soil; Water